2008
DOI: 10.3748/wjg.14.3642
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Transactivating Transcription-apoptin fusion protein induces apoptosis in hepatocellular carcinoma HepG2 cells

Abstract: AIM:To determine whether SP-TAT-apoptin induces apoptosis and also maintains its tumor cell specificity. METHODS: In this study, we designed a secretory protein by adding a secretory signal peptide (SP) to the N terminus of Transactivating Transcription (TAT)-apoptin (SP-TAT-apoptin), to test the hypothesis that it gains an additive bystander effect as an anti-cancer therapy. We used an artificial human secretory SP whose amino acid sequence and corresponding cDNA sequence were generated by the SP hidden Marko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
2
15
0
1
Order By: Relevance
“…This is consistent with the results of our previous study ( Fig. 1a) (9), indicating that a lentivirus-apoptin expression system is capable of dramatically up-regulating apoptin expression in HepG2 cells. Apoptin expression in HepG2 cells was further confirmed by Western blot analysis (Fig.…”
Section: Lentivirus-mediated Apoptin Expression In Hepg2 Cells Thesupporting
confidence: 82%
See 4 more Smart Citations
“…This is consistent with the results of our previous study ( Fig. 1a) (9), indicating that a lentivirus-apoptin expression system is capable of dramatically up-regulating apoptin expression in HepG2 cells. Apoptin expression in HepG2 cells was further confirmed by Western blot analysis (Fig.…”
Section: Lentivirus-mediated Apoptin Expression In Hepg2 Cells Thesupporting
confidence: 82%
“…in our previous study, we demonstrated that apoptin promoted HepG2 cell apoptosis by a secretory transactivating transcription-apoptin fusion protein system (9). in the present study, concurrent treatment of HepG2 radio-resistant cells with radiation and apoptin lentivirus was shown to further increase apoptotic cell death compared to either treatment alone, suggesting that apoptin sensitizes radio-resistant HepG2 cells to radiation.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations